The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1477-7525-9-112
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of health status do not change over three-year periods and exacerbation makes difference in chronic obstructive pulmonary disease

Abstract: BackgroundThe association between disease markers and health status (HS) overtime is unclear. The aim of this study was to verify the predictors of HS at baseline and after three years in Chronic Obstructive Pulmonary Disease (COPD) patients.MethodsNinety-five consecutive COPD patients (66% male, age = 67 ± 9 y, FEV1 = 58 ± 23%) underwent the following evaluations at baseline and after three years: body composition, pulse oximetry (SpO2), six-minute walk distance (6MWD), Modified edical Research Council dyspne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
4
7
1
1
Order By: Relevance
“…The DOSE (dyspnoea, obstruction, smoking, exacerbation) index 16 was found to predict changes in CCQ in a 2-year follow-up period, 17 and the BODE (BMI, obstruction, dyspnoea, exercise capacity) index 18 predicted change in SGRQ in a 3-year follow-up period. 19 In the latter study, the composite BODE index was also replaced by the included mono-components, with the result that dyspnoea and exacerbations but not BMI predicted change in health status. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DOSE (dyspnoea, obstruction, smoking, exacerbation) index 16 was found to predict changes in CCQ in a 2-year follow-up period, 17 and the BODE (BMI, obstruction, dyspnoea, exercise capacity) index 18 predicted change in SGRQ in a 3-year follow-up period. 19 In the latter study, the composite BODE index was also replaced by the included mono-components, with the result that dyspnoea and exacerbations but not BMI predicted change in health status. 19 …”
Section: Discussionmentioning
confidence: 99%
“… 19 In the latter study, the composite BODE index was also replaced by the included mono-components, with the result that dyspnoea and exacerbations but not BMI predicted change in health status. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Patients completed the questionnaires themselves, assisted by the researchers only when needed; support was strictly limited to reading out the questions. SGRQ has been used as the gold standard for measurement of health status in clinical studies and exacerbation of COPD 5,3032. However, exacerbation studies have assessed differences in health status over longer periods, from 1–6 months to 3 years 5,7,30,31.…”
Section: Discussionmentioning
confidence: 99%
“…SGRQ has been used as the gold standard for measurement of health status in clinical studies and exacerbation of COPD 5,3032. However, exacerbation studies have assessed differences in health status over longer periods, from 1–6 months to 3 years 5,7,30,31. However, the length and complex scoring algorithm required for the SGRQ makes it less feasible in routine daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patient characteristics cannot be compared directly due to different stratifications of the study population: Habraken et al 5 distributed their population into three equal-sized groups stratified by change in SGRQ total score, whereas we used the MCID as a cutoff point to identify clinically relevant changes. Ferrari et al 32 studied changes in health status in patients with mild to severe COPD and reported that disease-specific health status as assessed by SGRQ worsened (≥ 4%) in 51% of the patients and improved in 28% of the patients.…”
Section: One-year Changes In Disease-specific Health Statusmentioning
confidence: 99%